Active ageing in Asia - Walker, Alan, 1949-; Aspalter, Christian; Walker, Alan, 1949- . (Abingdon, Oxon ; New York, NY : Routledge, 2015)
'East Asian societies are changing rapidly, and one of the most important facets of this transformation is the ageing of society.'Active ageing' is one of the few concepts available today to effectively address the problems arising from a highly-aged and, particularly in East Asia, fast-ageing society, offering a new social policy paradigm to redirect and innovate new social policies, particularly social services, social transfers, social regulations and laws, towards more investment in and support of the fast rising number of elderly citizens. This book focuses on the experiences of East Asian societies where active ageing has been implemented. It presents a thorough analysis of the concept of active ageing and its potential and problems of implementations in different stages of development in East Asia, whilst providing theoretical clarity to, and broadening the concept of, active ageing. Further, the country-focused case studies explore how to design, pursue, measure and evaluate social policies, highlight the problems related to the implementation of the concept of active ageing in social policy and outline the practical implications of active ageing theory in policy making. Active Ageing in Asia will appeal to students and scholars of social and public policy, social work, gerontology and health and social administration, as well as to policy makers working in the field''--
The concept of active ageing / Alan Walker -- New perspectives for active ageing: the normative approach of developmental social policy / Christian Aspalter -- Active ageing in South Korea / Sung-Jae Choi -- Active ageing in Taiwan / Wan-I Lin and Ping-Hui Wu -- Active ageing in Hong Kong / Joe C.B. Leung -- Active ageing in mainland China / Vivian W.Q. Lou -- Active ageing in Malaysia / Sharifah Norazizan Syed Abdul Rashid -- Active ageing in Singapore / Kalyani K. Mehta --Active ageing in Indonesia / Evi Nurvidya Arifin -- The way forward for active ageing / Alan Walker and Christian Aspalter.
Includes bibliographical references and index.
Keywords: Aging -- Social aspects -- East Asia; Aging -- Government policy -- East Asia